Добір асортименту для прискореного розмноження інтродукованих деревних листяних рослин в Донбасі - Довбиш, Н.Ф. (Промышленная ботаника, 2003)
The results of investigation of the regenerative capacity in 70 species, forms and sorts of the introduced arboreal deciduous plants. are presented in the paper. A basic assortment (54 taxa) and an additional one (14 taxa) for the accelerated propagation in the nurseries, or by the specialists in urban forestry and amateur horticultura – lists are proposed.